The Influence of Exhibitors Brand Equity on the Purchase Intentions of Customers: Empirical Evidence from Kunming, Yunnan Province, China - Yi, Yuan (Journal of Ecohumanism, 2025)
The research evaluates the relationship between customer-based brand equity and the purchase intentions of customers in the exhibition industry of China. The research aims to identify key determinants of brand equity of the participating exhibitors and the association of these factors with the purchase intentions of the visitors or customers in the exhibition. The key research gap comprises lack of discussion on the association between key determinants of brand equity and purchase intentions of the customers. Thus, the current study fulfils this research gap by identifying five main determinants of customer-based brand equity of participating exhibitors in China Kunming International Stone Fair of 2023 and the purchase intentions of the customers. The findings suggest positive influence of brand image and association on the customers willingness to purchase exhibitors’ product which in turn improves their brand equity. The managerial implication of the study argues that social media marketing should be incorporated by exhibitors to improve their brand association and image. The main limitation of the analysis is geographical constraint which reduces the generalizability of the research findings to other countries and industries. Future studies can incorporate cross-country and cross-industry analysis to extend the upon the current study methodology.